Pengenalan Rangku Alu sebagai Permainan Tradisional untuk Menumbuhkan Kepedulian Mahasiswa Penjaskesrek Undana Terhadap Pelestarian Budaya Lokal - Fera Ratna Dewi Siagian; Fadhillah amaliyah Koko (PT. Penerbit Riset Sadwa, 2026)
Rangku Alu is a traditional game originating from East Nusa Tenggara and contains cultural, social, and educational values. However, this traditional game is increasingly less well-known among the younger generation, including students, due to the impact of globalization and technological advances. This Community Service Program (PkM) is designed to introduce the traditional game of Rangku Alu to students of Penjaskesrek Undana as a step to raise awareness of the preservation of local culture. The methods used in implementing the activity.include socialization, demonstrations, and direct practice of the Rangku Alu game. The results of this activity show an increase in students' knowledge, enthusiasm, and appreciative attitude towards local culture. This program has a positive influence in raising students' awareness of the importance of maintaining and preserving traditional games as part of the nation's cultural identity